Possible Benefits of a Low Protein Diet in Older Patients With CKD at Risk of Malnutrition: A Pilot Randomized Controlled Trial - Caldiroli, Lara; Vettoretti, Simone; Armelloni, Silvia; Mattinzoli, Deborah; Ikehata, Masami; Molinari, Paolo; Alfieri, Carlo; Messa, Piergiorgio; Castellano, Giuseppe (Frontiers in Nutrition, 2022)
Background:Current guidelines do not clarify whether older patients with advanced chronic kidney disease may benefit of low protein diet if they are at risk of malnutrition. We compared the effects of normo-calorie/normo-protein (NP) and normo-calorie/low protein diet (LP) on nutritional status and metabolic complications related to the progression of kidney damage in these patients. Methods: this pilot study had an open label randomized-controlled design (ClinicalTrials.gov Id: NCT05015647). Thirty-five patients were treated for six months with two different diets (LP=17) and (NP=18). Malnutrition was assessed by Malnutrition Inflammation Score and International Society of Renal Nutrition and Metabolism criteria. Renal function was assessed by creatinine and cystatin-C based eGFR. Results: at the end of the study Malnutrition Inflammation Score was improved in both LP and NP groups (respectively: 3±3 vs 6±1.5, p=0.020 and 3±2.5 vs 6±2, p=0.012), prevalence of protein energy wasting syndrome decreased only in LP. LP group had higher eGFRcys-C (17±6 vs 12±4 ml/min/1.73 m2; p<0.05), lower serum urea (105±65 vs 138±30 mg/dl; p<0.05) and lower PTH (68±10vs99±61 ng/L; p<0.05) than NP. Serum and urinary phosphorous did not change while FGF23-intact and FGF23 c-terminal increased in both groups (FGF23-intact in LP: 70[48;98] vs 126[90;410] pg/mL, p<0.01 and in NP: 86[57;194] vs 143[119;186] pg/mL, p<0.01; FGF23 c-terminal in LP: 77[30.3;112] vs 111[63;384] RU/mL, p<0.01 and in NP: 142[56.6;175] vs 157[76.7;281] RU/mL, p<0.01).(FGF23-intact in LP: 70±70 vs 126±274 pg/mL, p=0.0004 and in NP: 86±139 vs 143±65 pg/mL, p=0.0074; FGF23 c-terminal in LP: 77±83 vs 111±250 RU/mL, p<0.0001 and in NP: 142±218 vs 157±180 RU/mL, p<0.0001). Conclusions: LP diet has a favorable impact on nutritional status as much as NP diet with possible greater benefits on the progression of kidney disease and some of its metabolic complications.